The Biggest Auction Ever: the Sale of the British 3G Telecom Licenses. - Binmore, K; Klemperer, P (Nuffield College (University of Oxford), 2001)
This paper reviews the part played by economists in organizing the British third-generation mobile-phone licence auction that concluded on 27 April 2000. It raised $22 1/2 billion ($34 billion or 2 1/2% of GNP) and was widely described at the time as the biggest auction ever. We discuss the merits of auctions versus "beauty contests", the aims of the auction, the problems we faced, the auction designs we considered, and the mistakes that were made.